Experimental analysis of the energy performance of an ACTive, RESponsive and Solar (ACTRESS) façade module. (August 2016) - Favoino, Fabio; Goia, Francesco; Perino, Marco; Serra, Valentina
Highlights: The ACTRESS (ACTive, RESponsive and Solar) multifunctional façade module is presented. The monitoring campaign of the MFM module in an outdoor test cell is presented and discussed. The different performance indicators (component/whole MFM level) are detailed. The behaviour of the different components of the MFM is evaluated. The overall energy performance of the whole MFM is analysed under different boundary conditions. Abstract: Responsive Building Elements (RBEs) are technologies enabling the exploitation of the opportunities offered by the environment and of renewable energy sources at the building scale. Amongst RBE concepts, Advanced Integrated Façades (AIFs) is probably one of the most promising technologies. In fact important players in the field of the façade engineering have started to develop integrated modular façade systems (Multifunctional Façade Modules – MFMs), with a dynamic behaviour interacting with the other building services, to reduce the building energy use and maximize the indoor comfort conditions. In this framework, a research activity aimed at the development of solar and active building skins was carried out. A MFM has been conceived and a prototype realised for experimental evaluations. The work presented in this paper illustrates the outcomes of the experimental investigation of the MFM called ACTRESS (ACTive, RESponsive and Solar), which has been tested by means of an outdoor test cell apparatus. In the paper, the ACTRESS module is presented and its performance assessed by means of standardized and non-standardized building performance metrics. The results of the experimental campaign show an overall very good performance of the technology in terms of improved building energy efficiency, although some critical aspects are revealed too. Moreover the façade module shows a very high degree of adaptability, as different strategies and behaviours can be achieved according to the desired performance or requirements.